Language Shift (Global Journal of Human-Social Science, 2012)
This research is intended to ascertain the factors that are responsible for banishing Punjabi language and a corresponding adoption of English language though apparently the panoramic milieu is hostile to this shift Language shift is a societal trend and society formation is based on collaborative work of certain factors by following this line of reasoning a hypothesis is formed that language shift is burgeoned motivated and accelerated by an implicit working of historical cultural social economic and psychological factors In order to examine the validity of hypothesis data was collected through a self-administered questionnaire with a sample size of hundred people The result shows that these factors are involved though at varying degree in this germinating trend of shift from Punjabi to English language
Keywords: Ascertain; banishing